Aware Computing in Spatial Language Understanding Guided by Cognitively Inspired Knowledge Representation. (17th July 2012) - Yokota, Masao
Abstract : Mental image directed semantic theory (MIDST) has proposed an omnisensory mental image model and its description language L md . This language is designed to represent and compute human intuitive knowledge of space and can provide multimedia expressions with intermediate semantic descriptions in predicate logic. It is hypothesized that such knowledge and semantic descriptions are controlled by human attention toward the world and therefore subjective to each human individual. This paper describes L md expression of human subjective knowledge of space and its application to aware computing in cross-media operation between linguistic and pictorial expressions as spatial language understanding.